2018
DOI: 10.2147/ccid.s126850
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of rosacea with a focus on anxiety and depression

Abstract: BackgroundRosacea is a common, chronic skin condition characterized by facial redness and inflammatory lesions. The disease can lead to social stigmatization and may significantly reduce the quality of life of patients. Psychosocial impact of rosacea can be severe and debilitating; however, it is still underestimated.ObjectiveThis paper provides a literature review focused on depression and anxiety in patients with rosacea.ConclusionRosacea patients have an increased risk of developing depression and anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
3
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 28 publications
(36 reference statements)
0
20
3
4
Order By: Relevance
“…The condition may be aggravated by numerous triggers such as microorganisms, ultraviolet light, ethanol, nutrition, temperature extremes, psychosocial stress, and hormones . Symptoms of rosacea can lead to social stigmatization and can have a detrimental effect on the quality of life of affected patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition may be aggravated by numerous triggers such as microorganisms, ultraviolet light, ethanol, nutrition, temperature extremes, psychosocial stress, and hormones . Symptoms of rosacea can lead to social stigmatization and can have a detrimental effect on the quality of life of affected patients …”
Section: Introductionmentioning
confidence: 99%
“…3 Symptoms of rosacea can lead to social stigmatization and can have a detrimental effect on the quality of life of affected patients. 4,5 Several topical therapies are available for treating rosacea 6 ; however, they are unlikely to reduce telangiectasia. 3 Intense pulsed light (IPL) devices can successfully treat the clinical manifestations of rosacea that fail to respond to medical therapies, such as telangiectases and background centrofacial erythema.…”
mentioning
confidence: 99%
“…A survey of a cohort of patients with erythemotelangiectatic rosacea found that they experience a substantial negative impact of their disease on multiple quality of life instruments . Patients with rosacea have also shown an increased propensity for anxiety and depression …”
Section: Introductionmentioning
confidence: 99%
“…Розацеа -хроническое, рецидивирующее заболевание (как правило кожи лица), которое сопровождается воспалением, имеет полиэтиологическую природу и характеризуется прогредиентным течением, а также резистентностью к традиционной терапии [1][2][3][4][5][6]. Согласно клинико-статистическим данным, розацеа весьма распространена, составляя 5-20% в структуре дерматологической заболеваемости, причем за последние 10-15 лет этот показатель имеет стойкую тенденцию к повышению [1,2,7,8].…”
unclassified
“…Следует подчеркнуть и социальное значение розацеа, поскольку впервые заболевание начинается на третьем десятилетии жизни и достигает расцвета в 40-50 лет на видимых участках кожи с запуском пролиферативных процессов и формированием фим. Представление о собственной непривлекательности пагубно влияет на психику пациентов, приводя к тревоге и депрессии [4,7].…”
unclassified